Preparation method and application of porous carbon with dendritic pore structure

Porous carbon with dendritic pore structure was prepared by gradient heat treatment and activation of pore expansion using thermoplastic phenolic resin, polyester polyurethane and piperazine-containing aromatic polyamide in porous carbon materials, and the prior art was solved The problems of uneven pore size distribution and low porosity of porous carbon materials improve the cycle stability and capacitance of lithium batteries.

CN118954506BActive Publication Date: 2025-02-11BEIJING IAMETAL NEW ENERGY TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411440619.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-11
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, the pore size distribution of porous carbon materials is uneven and has low porosity, making it difficult to meet the requirements of the negative electrode materials of high-energy-density lithium-ion batteries.

Method used

Porous carbon with dendritic pore structure was prepared by gradient heat treatment and activation of pore expansion using thermoplastic phenolic resin, polyester polyurethane and piperazine-containing aromatic polyamide as sacrificial agents.

Benefits of technology

The stable structure, high porosity and appropriate pore size distribution of porous carbon materials are achieved, the deposition rate and dispersion uniformity of silicon are improved, and the cycle stability and capacitance of lithium batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954506B_ABST
    Figure CN118954506B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing porous carbon with a dendritic pore structure, comprising the following steps: (S1) dissolving a thermoplastic phenolic resin, a sacrificial agent, and a curing agent in a solvent to form a mixed solution, and then performing rotary evaporation and crushing to obtain solid particles; the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1: (0.6-0.8): (1.2-1.5); (S2) subjecting the solid particles to gradient heat treatment under an inert atmosphere to obtain a porous carbon precursor; (S3) subjecting the porous carbon precursor to activation and pore expansion to obtain porous carbon with a dendritic pore structure. The porous carbon with a dendritic pore structure prepared by the present invention has good cycle stability and high capacitance when used as a silicon-carbon negative electrode of a lithium battery after chemically depositing silicon and carbon coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and specifically relates to a preparation method and application of porous carbon with a dendritic pore structure. Background Art

[0002] The domestic lithium battery industry is entering a period of rapid development. The demand for new energy vehicles and drones has driven the pursuit of high energy density batteries. This trend plays a key role in promoting the popularization of new energy vehicles, realizing the transformation of energy structure and replacing fossil fuels with electricity. The battery industry is improving battery performance and reducing costs through technological innovation and large-scale production to meet the high standards of the market. Negative electrode materials are one of the important raw materials for lithium-ion batteries. Negative electrode materials have a great influence on the energy density, cycle performance, charge and discharge rate and low temperature performance of lithium-ion batteries.

[0003] The negative electrode materials currently used in lithium ions are mainly graphite-based, but the theoretical gram capacity of graphite negative electrodes is only 372mAh / g; while the theoretical gram capacity of silicon-based negative electrodes can be as high as 4200mAh / g; but the expansion rate of pure silicon-based negative electrode materials is as high as 300%, which will cause silicon to pulverize during the charging and discharging process, making its cycle performance far lower than that of graphite negative electrodes, only 300 to 500 cycles. In the prior art, the main direction of efforts is silicon-carbon composite materials, that is, using chemical vapor deposition to deposit silicon atoms into porous carbon materials to form silicon-carbon composite materials, which can effectively reduce the volume expansion of silicon. Carbon materials are compounded with high-capacity silicon materials to have high capacity and good conductivity. At the same time, the carbon layer can reduce the direct contact between silicon and the electrolyte, inhibit the growth of SEI film, and improve the cycle performance of the material.

[0004] For silicon-carbon negative electrode materials, the deposition uniformity and amount of silicon nanoparticles will greatly affect the performance of the negative electrode materials. The pore size distribution uniformity, stability and porosity of porous carbon materials prepared in the traditional activated carbon field still need to be further improved to meet the requirements of high-standard new silicon-carbon negative electrode materials. Therefore, it is of great significance to develop and prepare porous carbon with stable structure, high porosity and suitable pore size distribution.

[0005] In the prior art, porous carbon with suitable pore size distribution is hierarchical porous carbon. For example, Xu Jiankang et al. (Carbon, 2018, 1: 05-07) used cobalt acetate as a template and citric acid as a carbon source, and adopted a rapid heating and cooling process to prepare hierarchical porous carbon by a one-step template carbonization method. The obtained porous carbon has a typical mesopore-micropore hierarchical pore structure, with micropores concentrated at 0.8 nm and mesopores concentrated at 4 nm, and a specific surface area of ​​753 ~ 890 m 2 / g, but the specific surface area and porosity of the graded porous carbon are relatively low.

[0006] Patent CN118016879 A discloses a hierarchical porous carbon and its preparation method and application. The hierarchical porous carbon is composed of macropores, mesopores and micropores interconnected and connected to form a three-dimensional interconnected network cross-linked carbon skeleton, and a portion of the carbon in the network cross-linked carbon skeleton is graphitized to form a graphitized carbon network cross-linked skeleton; the preparation method includes the following steps: taking a carbon source, a porogen, and a solvent, mixing them, then removing the solvent, crushing, carbonizing in an inert gas atmosphere, then acid washing to remove the porogen, and finally washing and drying to obtain hierarchical porous carbon; the carbon source is coal tar and the porogen is zeolite. The pore size range of the macropores of the porous carbon prepared by this patent is greater than 50nm, the pore size range of the mesopores is 2-50nm, and the pore size range of the micropores is less than 2nm. Its pore size distribution is too wide, the hollow and macropores are both too large, and the overall specific surface area is low. Summary of the invention

[0007] In order to achieve the purpose of developing porous carbon with stable structure, high porosity and suitable pore size distribution, the present invention adopts the following technical scheme:

[0008] A method for preparing porous carbon with a dendritic pore structure comprises the following steps:

[0009] (S1) dissolving a thermoplastic phenolic resin, a sacrificial agent, and a curing agent in a solvent to form a mixed solution, and then performing rotary evaporation and crushing to obtain solid particles; the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1: (0.6-0.8): (1.2-1.5);

[0010] (S2) The solid particles are subjected to gradient heat treatment under an inert atmosphere to obtain a porous carbon precursor;

[0011] (S3) The porous carbon precursor is activated and expanded to obtain porous carbon with a dendritic pore structure.

[0012] The porous carbon with a dendritic pore structure provided in the present invention refers to a porous carbon with a central radial pore structure and a pore size that gradually increases from the inside of the particle to the surface of the particle. This pore structure has good connectivity, and when silicon is chemically vapor deposited, silicon particles can enter the inside of the porous carbon, making full use of all adsorption sites, thereby increasing the deposition rate of silicon and the uniformity of dispersion in the porous carbon, maintaining the stability of the electrode structure, and improving the cycle stability of the battery.

[0013] Furthermore, in step (S1), the mass ratio of the thermoplastic phenolic resin, the sacrificial agent and the curing agent is 1: (0.15-0.3): (0.03-0.06), preferably 1: (0.2-0.25): (0.03-0.06).

[0014] Furthermore, in step (S1), the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1: (0.7-0.8): (1.3-1.4).

[0015] Furthermore, in step (S1), the aromatic polyamide containing piperazine structure is prepared by reacting piperazine and aromatic dibasic acid chloride, and the molar ratio of piperazine to aromatic dibasic acid chloride is (1.05-1.15):1; for example, 1.1:1. The aromatic dibasic acid chloride is at least one of terephthaloyl chloride or isophthaloyl chloride.

[0016] Furthermore, the aromatic polyamide containing piperazine structure is obtained by a preparation method comprising the following steps:

[0017] (L1) dissolving anhydrous piperazine and anhydrous carbonate in a solvent to form solution A; dissolving dibasic acid chloride in a solvent to form solution B;

[0018] (L2) Solution B and solution A are mixed, and reacted at 3-10° C. for 4-8 hours under an inert atmosphere to obtain a reaction mixture;

[0019] (L3) The reaction mixture is filtered and vacuum dried to obtain an aromatic polyamide containing a piperazine structure.

[0020] Preferably, in step (L1), the mass ratio of anhydrous piperazine to anhydrous carbonate is 1:(1.5-2); the total concentration of solution A is 20wt%-30wt%, and the concentration of solution B is 10 wt%-20wt%. The amounts of solution A and solution B are such that the molar ratio of piperazine to aromatic dibasic acid chloride is (1.05-1.15):1.

[0021] Preferably, in step (L1), the anhydrous carbonate is anhydrous K 2 CO 3 or anhydrous Na 2 CO 3 ; The solvent is at least one of N,N′-dimethylacetamide (DMAC), N,N′-dimethylformamide (DMF), and N-methylpyrrolidone (NMP).

[0022] Preferably, in step (L2), the inert atmosphere is at least one of nitrogen or argon.

[0023] Preferably, in step (L3), the vacuum drying is performed at 50-70° C. for 12-24 hours.

[0024] Furthermore, in step (S1), the number average molecular weight of the thermoplastic phenolic resin is 1500-5000; the number average molecular weight of the polyester polyurethane is 5000-20000; the number average molecular weight of the polymethyl methacrylate is 5000-15000; and the number average molecular weight of the aromatic polyamide containing a piperazine structure is 3000-5000.

[0025] Furthermore, in step (S1), the curing agent is at least one of hexamethylenetetramine, trimethylhexamethylenediamine, diethylaminopropylamine, 3,4-diaminothiophene, and 3,4-diaminothieno[2,3-B]thiophene-2,5-dicarbonitrile; preferably 3,4-diaminothiophene.

[0026] Furthermore, in step (S1), the solvent is any one of methanol, ethanol and acetone; and the crushing is to crush to 100-400 mesh.

[0027] Furthermore, in step (S2), the gradient heat treatment is first heat treated at 150-250°C for 1-3 hours, then heat treated at 270-300°C for 2-4 hours, then heat treated at 320-400°C for 2-4 hours, and finally heat treated at 600-900°C for 1-4 hours.

[0028] Furthermore, in step (S2), the inert atmosphere is nitrogen, argon or helium.

[0029] Furthermore, in step (S3), the activating agent is at least one of water vapor, carbon dioxide, ammonia, and hydrogen sulfide; and the activation conditions are: temperature 800°C~1000°C, time 4h~8h.

[0030] In a second aspect, the present invention provides a porous carbon with a dendritic pore structure, which is prepared by the aforementioned preparation method.

[0031] In the third aspect, the present invention provides a silicon-carbon negative electrode, which is prepared by vapor-depositing silicon and carbon coating the porous carbon with a dendritic pore structure obtained by the above-mentioned preparation method. The processes of vapor-depositing silicon and carbon coating are well known to those skilled in the art, such as using an organic silicon source gas for vapor-depositing silicon, the organic silicon source gas is selected from at least one of silane, dichlorodihydrosilane, trichlorosilane, silicon tetrachloride, silicon tetrafluoride, disilane, etc.; if a carbon source gas is used for carbon coating, the carbon source gas is selected from at least one of C1-4 alkanes, C2-4 alkenes, and C2-4 alkynes.

[0032] The mechanism of the present invention is described as follows:

[0033] Phenolic resin is a heat-stable polymer with a high decomposition temperature. Its structure contains active phenolic hydroxyl and hydroxymethyl groups and has a high residual carbon rate. It is an ideal carbon-forming polymer. The sacrificial agent is a heat-unstable polymer. After mixing with the phenolic resin, a phase separation structure is formed. The sacrificial agent can undergo thermal decomposition at a relatively low temperature and be released in the form of small molecular gas, thereby forming pores in the mixed system. The present invention uses polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing piperazine structure in a mass ratio of 1: (0.6~0.8): (1.2~1.5) as sacrificial agents and conducts gradient heat treatment with thermoplastic phenolic resin. The inventors have found through research that the matching of the three can produce porous carbon with a stable dendritic channel structure. The possible reason is that the urethane groups on the main chain of the polyester polyurethane break from the CO bond in the range of 150-180°C and decompose to produce isocyanate, which can cross-link with the thermoplastic phenolic resin in this temperature range to improve its density; as the temperature rises to around 250°C, the remaining groups on the main chain of the polyester polyurethane decompose to produce CO 2 Small molecular gases such as olefins escape from the matrix, leaving pores; polyester polyurethane can thermally decompose to produce more CO than polyether polyurethane. 2 , which is more beneficial to improving the porosity. The polymethyl methacrylate in the sacrificial agent can decompose at 270~300℃ to produce small molecules and gases, thereby generating pores in the matrix; the aromatic polyamide containing piperazine structure has good thermal stability due to the simultaneous existence of piperazine structure and aromatic groups, and can decompose at 300~400℃ to produce small molecules and gases, thereby further generating pores in the matrix. In summary, the combined action of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing piperazine structure realizes hierarchical pore formation at different temperatures, thereby generating porous carbon with dendritic pore structure. At the same time, since the decomposition product of polyester polyurethane at 150~180℃, isocyanate, can cross-link and cure the thermoplastic phenolic resin with the curing agent to form a dense cross-linked network structure, and then when it is further increased to 600~900℃ for carbonization, a porous carbon with a stable dendritic pore structure is formed. In addition, the aromatic polyamide containing piperazine structure has a high nitrogen content and realizes nitrogen atom doping of porous carbon, which is beneficial to improve its electrochemical performance and extend the cycle life.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention uses a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure as a sacrificial agent to perform gradient heat treatment with thermoplastic phenolic resin to achieve decomposition and pore formation at different temperatures; at the same time, the isocyanate decomposition product of the polyester polyurethane at low temperature can cross-link and cure the thermoplastic phenolic resin together with the curing agent; and finally, a porous carbon with a stable structure and a high porosity dendritic channel structure is obtained, which provides a basis for further vapor deposition of silicon to prepare a silicon-carbon negative electrode.

[0036] 2. The pore size distribution of the porous carbon with a dendritic pore structure prepared by the present invention is: micropores <2nm account for 75~85%, mesopores 2-10nm account for 10~20%, and pores above 10nm account for 3~7%; under this proportion condition, pores above 10nm serve as the trunk, mesopores 2~10nm serve as branches, and micropores <2nm serve as branches, thus forming a porous carbon with a dendritic pore structure.

[0037] 3. The porous carbon with a dendritic pore structure prepared by the present invention, when used as a silicon-carbon negative electrode of a lithium battery after chemically deposited silicon and carbon coating, has good cycle stability and high capacity. Its first reversible specific capacity is above 1900 mAh / g, its first efficiency is above 90, and its capacity retention rate after 100 cycles at 0.1C can reach above 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A schematic diagram of the pore structure of porous carbon with a dendritic pore structure prepared in the present invention;

[0039] Figure 2 is the nitrogen adsorption isotherm curve of the dendritic porous carbon prepared in Example 1;

[0040] Figure 3 : is the pore size distribution diagram of the dendritic porous carbon prepared in Example 1;

[0041] Figure 4 This is a distribution diagram of the pore size ratio of the dendritic porous carbon obtained in Example 1;

[0042] Figure 5 This is the first cycle charge and discharge curve of a lithium battery assembled with the silicon-carbon negative electrode material of Application Example 1 at a rate of 0.1C. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0044] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0045] Thermoplastic phenolic resin, polyester polyurethane and polymethyl methacrylate were all purchased from Aladdin, wherein the number average molecular weight of the thermoplastic phenolic resin was 3000, the number average molecular weight of the polyester polyurethane was 12000, and the number average molecular weight of the polymethyl methacrylate was 10000.

[0046] Preparation of aromatic polyamide containing piperazine structure

[0047] Preparation Example 1

[0048] (L1) 94.75 g (1.1 mol) of anhydrous piperazine and 150 g of anhydrous Na 2 CO 3 Dissolve in 700 g of N,N′-dimethylacetamide (DMAC) to form solution A; dissolve 203.02 g (1 mol) of phthaloyl chloride in 900 g of DMAC to form solution B;

[0049] (L2) Slowly add solution B to mixed solution A over 1-2 hours, and stir at 5±1°C for 6 hours under nitrogen protection to obtain a reaction suspension;

[0050] (L3) The reaction suspension was filtered and vacuum dried at 60° C. for 12 h to obtain an aromatic polyamide containing a piperazine structure.

[0051] The number average molecular weight was determined by gel permeation chromatography to be about 4300.

[0052] Example 1

[0053] (S1) dissolving 10 kg of thermoplastic phenolic resin, 1.5 kg of sacrificial agent, and 0.3 kg of curing agent hexamethylenetetramine in acetone to form a mixed solution, and then performing rotary evaporation and crushing to 200 meshes to obtain solid particles; the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1:0.6:1.2;

[0054] (S2) placing the solid particles in an activation furnace, heating the solid particles to 170°C at a heating rate of 5°C / min in a nitrogen atmosphere and keeping the temperature for 2 h, then heating the solid particles to 280°C and keeping the temperature for 2 h, then heating the solid particles to 350°C and keeping the temperature for 2 h, and finally heating the solid particles to 800°C and keeping the temperature for 3 h, to obtain a porous carbon precursor;

[0055] (S3) Turn off the nitrogen gas, and then evenly introduce 1.4 kg of water vapor within 6 hours. After the water vapor ventilation is completed, switch to a nitrogen atmosphere and cool it to room temperature to obtain a porous carbon with a dendritic pore structure.

[0056] Figure 1 This is a schematic diagram of the pore structure of the porous carbon with a dendritic pore structure prepared by the present invention.

[0057] Example 2

[0058] The rest is the same as Example 1, except that in step (S1), the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1:0.7:1.3.

[0059] Example 3

[0060] The rest is the same as Example 1, except that in step (S1), the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1:0.8:1.4.

[0061] Example 4

[0062] The rest is the same as Example 1, except that in step (S1), the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1:0.8:1.5.

[0063] Example 5

[0064] The rest is the same as Example 2, except that in step (S1), the amount of the sacrificial agent is 2 kg, and 0.4 kg of 3,4-diaminothiophene is used instead of 0.03 g of hexamethylenetetramine.

[0065] Example 6

[0066] The rest is the same as Example 5, except that in step (S1), the amount of the sacrificial agent is 2.5 kg, and the amount of the curing agent 3,4-diaminothiophene is 0.5 kg.

[0067] Example 7

[0068] The rest is the same as Example 5, except that in step (S1), the amount of the sacrificial agent is 3 kg, and the amount of the curing agent 3,4-diaminothiophene is 0.6 kg.

[0069] Comparative Example 1

[0070] The rest is the same as Example 1, except that in step (S1), the sacrificial agent is a compound of polymethyl methacrylate and aromatic polyamide containing a piperazine structure in a mass ratio of 1:2, that is, the sacrificial agent does not contain polyester polyurethane.

[0071] Comparative Example 2

[0072] The rest is the same as Example 1, except that in step (S1), the sacrificial agent is a mixture of polyester polyurethane and polymethyl methacrylate in a ratio of 1:0.6, that is, the sacrificial agent does not contain aromatic polyamide with a piperazine structure.

[0073] Comparative Example 3

[0074] The rest is the same as Example 1, except that in step (S2), the temperature is increased to 800°C at a heating rate of 5°C / min and kept at that temperature for 3h, that is, a one-step heat treatment is adopted instead of a gradient heat treatment.

[0075] Application Example 1

[0076] The porous carbon with a dendritic pore structure obtained in Example 1 is subjected to chemical vapor deposition and carbon coating to form a silicon-carbon negative electrode material; the silicon-carbon negative electrode material is then applied to the negative electrode of a lithium-ion battery, assembled into a lithium battery, and its electrochemical performance is tested. Specific method: Silicon-carbon negative electrode material, Super P, carbon nanotubes and carboxymethyl cellulose and styrene-butadiene rubber composite binder are mixed in a mass ratio of 80:9.8:0.2:10 to form a slurry (the mass ratio of CMC and SBR is 1:1), and the slurry is applied to the copper foil with a 200μm thick scraper. After drying in a drying room, it is placed in a vacuum dryer for 12 hours to prepare a silicon-based negative electrode plate; then metal lithium is used as the counter electrode, polyolefin is used as a separator, 1mol / L LiPF6 (the solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) is used as the electrolyte, and 2% VC and 5% FEC are added to the electrolyte. The button battery is assembled in an argon atmosphere Braun inert gas glove box in Germany. The above-assembled battery is charged and discharged on a LAND charge and discharge tester. The charge and discharge range is 50 mV ~ 1.5 V, and the compaction density is 1.1 g / cm 3 After three charge and discharge cycles at a current density of 0.1 C (1 C = 1500 mA / g), rate charge and discharge tests were carried out at current densities of 1C and 5C, respectively.

[0077] Application Example 2-7

[0078] Other conditions are the same as those in Application Example 1, except that the dendritic porous carbon is prepared according to Examples 2-7 respectively.

[0079] Comparative Application Examples 1-3

[0080] Other conditions are the same as those in Application Example 1, except that the dendritic porous carbons are prepared according to Comparative Examples 1-3 respectively.

[0081] Testing and analysis

[0082] 1) Pore size distribution measurement: According to the gas adsorption BET method of GB / T19587-2017, a Tristar II 3020 fully automatic specific area and pore size analyzer produced by Micromeritics Instrument Corporation of the United States was used to perform a low-temperature nitrogen adsorption experiment on the dendritic porous carbon prepared in the embodiment and the comparative example to measure its pore size distribution. The data are shown in Table 1.

[0083] The nitrogen adsorption isotherm of the dendritic porous carbon prepared in Example 1 is as follows: Figure 2 Its pore size distribution diagram is shown in Figure 3 As shown; the distribution diagram of each aperture ratio is as follows Figure 4 shown.

[0084] Table 1 Pore size distribution of dendritic porous carbon

[0085] .

[0086] It can be seen from Table 1 that compared with the comparative example, the specific surface area of ​​the porous carbon prepared by the preparation method of the present invention is as high as 1800 m 2 / g or above; the pore size distribution range is: micropores <2nm account for 75~85%, mesopores 2-10nm account for 10~20%, and pores above 10nm account for 3~7%; under this proportion condition, pores above 10nm serve as the trunk, mesopores 2-10nm serve as the branches, and micropores <2nm serve as the branches, thus forming a porous carbon with a dendritic pore structure.

[0087] In Comparative Example 1, although the proportion of micropores <2 nm is relatively high, the pore size ratio above 10 nm is too low to form a dendritic pore structure; and the overall specific surface area is low, indicating that the overall porosity is low.

[0088] In Comparative Example 2, the microporosity <2 nm is relatively low and the overall specific surface area is low.

[0089] In Comparative Example 3, although the specific surface area is relatively high, the proportion of pores larger than 10 nm is relatively large, and the proportion of pores with a diameter of 2-10 nm is relatively small, and it is difficult to form a dendritic pore structure. This shows that only a compound sacrificial agent matched with gradient heat treatment can prepare porous carbon with a dendritic pore structure with a high specific surface area.

[0090] 2) Electrochemical performance test: The batteries assembled in the application example and the comparative example were charged and discharged on a LAND charge and discharge tester, with a voltage range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm 3 The battery performance test data is shown in Table 2.

[0091] Figure 5 This is the first cycle charge and discharge curve of a lithium battery assembled with the silicon-carbon negative electrode material of Application Example 1 at a rate of 0.1C.

[0092] Table 2 Electrochemical performance test

[0093] .

[0094] It can be seen from the data in Table 2 that when the dendritic porous carbon prepared by the preparation method of the present invention is used as the negative electrode of a lithium battery, its first reversible capacity is above 1900 mAh / g, the first coulombic efficiency is above 90%, and the capacity retention rate after 100 cycles at 0.1C is above 90%, indicating that the assembled lithium battery has good cycle stability and high capacity.

[0095] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A method for preparing porous carbon with a dendritic pore structure, characterized in that: The following steps are involved: (S1) dissolving a thermoplastic phenolic resin, a sacrificial agent, and a curing agent in a solvent to form a mixed solution, and then performing rotary evaporation and crushing to obtain solid particles; the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1: (0.6-0.8): (1.2-1.5); (S2) The solid particles are subjected to gradient heat treatment under an inert atmosphere to obtain a porous carbon precursor; (S3) The porous carbon precursor is activated and expanded to obtain porous carbon with a dendritic pore structure.

2. The preparation method according to claim 1, characterized in that: In step (S1), the mass ratio of the thermoplastic phenolic resin, the sacrificial agent and the curing agent is 1: (0.15-0.3): (0.03-0.06).

3. The preparation method according to claim 1 or 2, characterized in that: In step (S1), the mass ratio of the thermoplastic phenolic resin, the sacrificial agent, and the curing agent is 1: (0.2-0.25): (0.03-0.06).

4. The preparation method according to claim 1, characterized in that: In step (S1), the sacrificial agent is a compound of polyester polyurethane, polymethyl methacrylate, and aromatic polyamide containing a piperazine structure in a mass ratio of 1: (0.7-0.8): (1.3-1.4).

5. The preparation method according to claim 1, characterized in that: In step (S1), the aromatic polyamide containing piperazine structure is prepared by reacting piperazine and aromatic dibasic acid chloride, and the molar ratio of piperazine to aromatic dibasic acid chloride is (1.05-1.15):1; the aromatic dibasic acid chloride is at least one of terephthaloyl chloride and isophthaloyl chloride.

6. The preparation method according to claim 1, characterized in that: The aromatic polyamide containing piperazine structure is obtained by a preparation method comprising the following steps: (L1) dissolving anhydrous piperazine and anhydrous carbonate in a solvent to form solution A; dissolving dibasic acid chloride in a solvent to form solution B; (L2) Solution B and solution A are mixed, and reacted at 3-10° C. for 4-8 hours under an inert atmosphere to obtain a reaction mixture; (L3) The reaction mixture is filtered and vacuum dried to obtain an aromatic polyamide containing a piperazine structure.

7. The preparation method according to claim 6, characterized in that: In step (L1), the mass ratio of anhydrous piperazine to anhydrous carbonate is 1:(1.5-2); the total concentration of solution A is 20wt%-30wt%, and the concentration of solution B is 10wt%-20wt%; the amounts of solution A and solution B are such that the molar ratio of piperazine to aromatic dibasic acid chloride is (1.05-1.15):1; and / or In step (L1), the anhydrous carbonate is anhydrous K2CO3 or anhydrous Na2CO3; the solvent is at least one of N,N′-dimethylacetamide (DMAC), N,N′-dimethylformamide (DMF), and N-methylpyrrolidone (NMP); and / or In step (L2), the inert atmosphere is at least one of nitrogen or argon; and / or In step (L3), the vacuum drying is performed at 50-70° C. for 12-24 hours.

8. The preparation method according to claim 1, characterized in that: In step (S1), the number average molecular weight of the thermoplastic phenolic resin is 1500-5000; the number average molecular weight of the polyester polyurethane is 5000-20000; the number average molecular weight of the polymethyl methacrylate is 5000-15000; the number average molecular weight of the aromatic polyamide containing piperazine structure is 3000-5000; and / or In step (S1), the curing agent is at least one of hexamethylenetetramine, trimethylhexamethylenediamine, diethylaminopropylamine, 3,4-diaminothiophene, and 3,4-diaminothieno[2,3-B]thiophene-2,5-dicarbonitrile; the solvent is any one of methanol, ethanol, and acetone; and the crushing is to crush to 100-400 meshes.

9. The preparation method according to claim 1, characterized in that: In step (S2), the gradient heat treatment is first heat treatment at 150-250°C for 1-3 hours, then heat treatment at 270-300°C for 2-4 hours, then heat treatment at 320-400°C for 2-4 hours, and finally heat treatment at 600-900°C for 1-4 hours; and / or In step (S3), the reagent for activating and expanding the pores is at least one of water vapor, carbon dioxide, ammonia, and hydrogen sulfide; and the activation conditions are: temperature 800° C. to 1000° C., time 4 h to 8 h.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material and preparation method thereof

    CN114649523A